DOI: 10.29007/cthk
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality Application to Enhance Training of Lumbar Puncture Procedure: Preliminary Results

Abstract: With the recent rapid development of Augmented Reality (AR) headsets, new possi- bilities emerge for applications of AR technologies. Today, publicly available AR headsets provide novel storytelling platforms, expand the vision of doctors and engineers, remove boundaries of educational processes and assist humanity in multiple endeavors.Our research encompasses various levels of the learning process by examining design principals and developing reliable software for multiple educational applications. This pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…viewing educational content using a head-mounted device) was not considered specific to teaching neuraxial procedures. [20] The characteristics of the included evidence are displayed in table 2. Clinical use of XR was infrequent, with only four of 38 completed studies reporting the use of XR in patient care.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…viewing educational content using a head-mounted device) was not considered specific to teaching neuraxial procedures. [20] The characteristics of the included evidence are displayed in table 2. Clinical use of XR was infrequent, with only four of 38 completed studies reporting the use of XR in patient care.…”
Section: Resultsmentioning
confidence: 99%
“…viewing educational content using a head-mounted device) was not considered specific to teaching neuraxial procedures. [20]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, with the development of science and technology and the progress of medicine, MR technology has been gradually applied in several medical fields, such as diagnosis, surgery, rehabilitation treatment, education, and training. [21][22][23][24][25][26] Freschi et al found that MR could improve ultrasound probe manipulation training, with a success rate for visualizing the target structure of 78% in the hybrid group versus 45% in the physical group (P=0.04). 27 Wang et al presented an augmented reality navigation system for dental surgery based on a 3D image overlay.…”
Section: Discussionmentioning
confidence: 99%
“…The lumbar puncture (LP) is an invasive procedure where the physician inserts a thin needle into in the lumbar region, passing through different tissues, piercing the dura and accessing to the subarachnoid space [1]. This procedure is used for treatment, such as drug delivery or cerebrospinal fluid (CSF) removal to decrease intracranial pressure; and for diagnosis through the CSF sampling [1], [2].…”
Section: Introductionmentioning
confidence: 99%